Novel αβ Integrin-Targeted Peptide Probes for Prostate Cancer Imaging - Chiun-Wei Huang; Zibo Li; Hancheng Cai; Tony Shahinian; Peter S. Conti (Molecular Imaging)
Accumulating experimental evidence indicates that overexpression of α 2 β 1 integrin may correlate with progression in human prostate cancer. The objective of this study was to design a novel imaging probe based on the Asp-Gly-Glu-Ala (DGEA) peptide for near-infrared-fluorescent (NIRF) imaging of α 2 β 1 , integrin expression in prostate cancer. The peptides were conjugated with appropriate fluorescent dyes, and the binding affinity of these probes was evaluated by flow cytometry in three human prostate cell lines (PC-3, CWR-22, and LNCaP). In vivo NIRF imaging of the α 2 β 1 -positive PC-3 xenograft model was performed to evaluate the α 2 β 1 targeted probe. In vitro immunofluorescence staining was carried out to confirm the α 2 β 1 integrin expression level. Flow cytometry analysis showed that PC-3 had the highest probe uptake, followed by CWR-22 and LNCaP tumor cells. In the subcutaneous PC-3 model, the tumor demonstrated prominent uptake with good tumor to background contrast. Immunohistochemistry staining also supported the in vivo optical imaging results. DGEA-based optical agents have been developed for specific imaging of α 2 β 1 , integrin expression. In vitro and in vivo localization demonstrated the potential of this agent to identify tumor subtypes amenable to anti-α 2 β 1 integrin treatment and potentially provide prognostic information regarding tumor progression.